A REPRESENTAÇÃO TRIDIMENSIONAL FÍSICA E A ERGONOMIA NO PROJETO DE PRODUTOS: A VISÃO DE PROFESSORES, ESTUDANTES E PROFISSIONAIS DO DESIGN. - MAIA, Paula dos Santos (2019)
This research aims to understand the contribution of three-dimensional physical representation and ergonomics in product design from the perspective of student’s professors and design professionals. The methodology adopted is based on exploratory-descriptive research being a qualitative study with a bibliographical survey analysis of examples that stimulate the understanding interviews and questionnaires. Thus the study pointed out that there are differences regarding the use of physical three-dimensional representation and Ergonomics in the Academy and in the Market, depending on the purpose in product design projects. The results suggest that the subject factor was considered the most influential in the choice of 3D physical representations followed by the execution time and the technology available to produce them. And both physical and digital 3D representations are used to obtain product ergonomics information however with emphasis on the use of physical 3D representations by the Academy. We consider the contribution of this study to point out the main differences in students' teachers' and designers' view on three-dimensional representation and consequently a better and wider comprehension in the technical understanding of representations in the design field of Design.